Public Expenditures and Agricultural Growth in Burkina Faso - Ouedraogo , Souleymane; Bako , Daman (Asian Journal of Agriculture and Rural Development, 2014)
This study analyzes public funding in the agricultural sector in Burkina Faso and assesses its impact on agricultural growth. Based on data collected from several sources (finance acts over the period 1983-2008, Automated Prediction Instrument (IPA), World Bank and National agricultural statistics over 26 years (from 1983 to 2008), the agricultural production has been modelled by using an error correction model and Cobb-Douglas function. The econometric analysis results show that public funding has a positive impact on agricultural production in the short term. A 9% growth rate of public funding over the period 2009-2015, causes an average agricultural production of 6.75% over the period. So, it is necessary for the State to increase funding in the agricultural sector to achieve a better growth of the domestic production and to meet the Millennium Development Goals regarding hunger reduction over the period 2009-2015.